Study to identify the status and socio-economic developmental needs of Kpg. Pusa, Betong / Jelani Razali, Chong Vui Hok and Abdul Jabbar Abdullah - Razali, Jelani; Vui Hok, Chong; Abdullah, Abdul Jabbar (2006)
Economic development is important and desirable because it represent the means to uplift the income and living standard of the people of a country. As far as possible, the fruits of economic development should be equally enjoyed by all spectra of society to avoid the occurrence ofsocial and other undesirable problems. Nevertheless, the problem of inequality continues to exist in many countries, especially between the rural and urban population. This research project is conducted amongst others, to assess the socio-economic status of the residents of Kampong Pusa in Betong division of Sarawak and to determine the actions that can be taken by the government to up-lift their socio-economic status. The study found that the problem of poverty is relatively serious in the village with the average monthly income of households at only RM384.35. 86.70% of the households lived below the official poverty line income while a staggering 48.8% could be classified as hardcore poor with monthly incomes of less than RM300 a month.